Soil-based services in the built environment: A report prepared for the Department of Environment, Food and Rural Affairs - Wood, Gavin; Kibblewhite, Mark G.; Hannam, Jacqueline A.; Harris, Jim A.; Leeds-Harrison, Peter B. (Cranfield University, National Soil Resources Institute, 2005)
Background: Publication of the First Soil Action Plan for England in 2004 has drawn attention to the value that can be derived from the protection and appropriate management of the country’s soil resources. This principle applies all soils equally including those in built environments which are the subject of this report. Soil is valuable because it underpins both quality of life and biodiversity conservation. It does this by providing a range of services or functions which meet human needs and sustain natural systems. The principal of these are environmental regulation and environmental maintenance, food and fibre production, above and below ground habitat maintenance as support for biodiversity, protection of cultural services and provision of a platform for the built environment. Soil is, in practical terms, a non-renewable resource which can be destroyed by construction. To help protect soils in the built environment, the services they can and do provide to both society and the environment need to be documented and explained. This report proposes a framework to help explain soil’s services and functions within built environments and provides a literature-based review of those services, their current perceived value, and a risk assessment of the threats that may degrade them.